Omics technologies to understand drug toxicity mechanisms. Issue 11 (November 2022) - Nguyen, Nhan; Jennen, Danyel; Kleinjans, Jos
Highlights: High throughput technologies (HTPs) provide quantitative and multi-dimensional omics data. Available HTPs can capture biological alterations in DNA, RNA, protein, and metabolites. HTPs can resolve the traditional obstacles of orthodox drug toxicity approaches. Multi-omics analysis is a powerful approach to unveil cellular disturbances under drug treatment. Single-cell HTPs offer promising directions in adverse drug effect research. Abstract : Drug side effects are an important study subject in pharmacology. Recent omics technologies provide a range of omics data and help to understand the biological mechanisms involved in drug effects. These modern technologies provide significant support to all biological disciplines, including drug toxicology. In this review, we provide an overview the use of omics applications to understand drug side effects at the molecular level. We discuss by available omics technologies, their possible uses, as well as their advantages and limitations.